Two Sides of the Same Coin: How Do Different Dimensions of Product Program Innovativeness Affect Customer Loyalty?1. Issue 3 (2nd April 2013) - Stock, Ruth Maria; Zacharias, Nicolas A.
<x xml:space="preserve">Abstract</x> Conventional wisdom holds that innovativeness has essentially positive performance implications. However, empirical research reveals mixed findings regarding customer‐related responses to innovation, as distinct dimensions—such as product newness and meaningfulness—may generate responses in different manners. This study introduces a multidimensional conceptualization of innovativeness at the program level, thereby enlarging the customary perspective by considering both positive and negative customer responses to innovativeness. Drawing on information economics, this study suggests that product program meaningfulness fosters customer loyalty, whereas product program newness undermines customer loyalty. In addition, the study examines mechanisms that might buffer the negative newness–loyalty relationship and explores enablers of the positive meaningfulness–loyalty effect by considering a brand's association with innovativeness and customer integration. Empirical support for the proposed effects comes from a multi‐industry sample with 180 triadic cases from business‐to‐business companies, which includes assessments from marketing, and research and development managers as well as customers. Moderated regression analysis was applied to test the hypotheses. The results indicate a negative effect of product program newness on customer loyalty and a positive effect of product program meaningfulness. Further, a brand's close association with innovativeness reduces the negative effect of product newness, and integrating customers into the value‐creating process fosters the loyalty effect of product meaningfulness. This study offers a potential explanation for the ambiguity created by equivocal empirical results regarding customer responses to innovativeness. The study also shows that offering more innovations does not necessarily make customers loyal. Instead, managers should mitigate the negative effects of product program newness.